Program Magrib Mengaji To Reduce Drug Abuse Behavior Among Adolescents: A Qualitative Study In Binjai City - Khairina, Khairina; Muhammad Putra Dinata Saragi (IJGIE (International Journal of Graduate of Islamic Education), 2026)
Drug abuse among adolescents is a serious issue that threatens their health, morality, and the future of young generations, including in Binjai City. This study aims to examine the role of the Magrib Mengaji (Qur’an recitation at dusk) program as a religion-based preventive strategy in reducing drug abuse behavior among adolescents. The study employs a qualitative method using a case study approach to gain an in-depth understanding of the meaning and role of Magrib Mengaji in preventing drug abuse. Data were collected through observation, structured interviews with BNN (National Narcotics Board) staff, mosque leaders, and adolescents, as well as documentation. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation of sources and methods. The findings show that Magrib Mengaji helps shape religious character, enhance self-control, and strengthen a positive social environment for adolescents, thus keeping them away from drug influence. Community-based religious activities prove to have significant preventive effectiveness and can serve as an alternative model for drug prevention policies in society.